JEJAK MU’ALAF TIONGHOA HAJI BAMBANG SUJANTO (HAJI LIU MIN YUAN) SOSOK DISIPLIN DAN PEKERJA KERAS: MENCARI KEYAKINAN AGAMANYA (KAJIAN PERILAKU MAKNA KONVERSI KE AGAMA ISLAM) - Bambang Amir Alhakim (Discovery, 2023)
This research focuses on the conversion behavior of a Chinese Mu'alaf who is known as an important figure among the East Java Chinese ethnic group. He is Haji Bambang Sujanto or known by his Chinese name Haji Liu Min Yuan, Chairman of the Haji Muhammad Cheng Hoo Surabaya Foundation as well as one of the important figures of PITI (Pebina Iman Tauhid Islam) East Java. The important thing that needs to be underlined in this research is to find the meaning behind the act of converting to Islam from Haji Bambang Sujanto (Haji Liu Min Yuan) so that later lessons can be learned as life lessons on how the problem of religious belief is very fundamental in one's life to seek happiness. essential. As a study, this journal reveals individual phenomena and their social meaning after making changes in religious understanding (conversion) which then have implications or continue with more meaningful individual and social actions (behavior).